2017
DOI: 10.1186/s12866-016-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial microbiota of Kazakhstan cheese revealed by single molecule real time (SMRT) sequencing and its comparison with Belgian, Kalmykian and Italian artisanal cheeses

Abstract: BackgroundIn Kazakhstan, traditional artisanal cheeses have a long history and are widely consumed. The unique characteristics of local artisanal cheeses are almost completely preserved. However, their microbial communities have rarely been reported. The current study firstly generated the Single Molecule, Real-Time (SMRT) sequencing bacterial diversity profiles of 6 traditional artisanal cheese samples of Kazakhstan origin, followed by comparatively analyzed the microbiota composition between the current data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
(61 reference statements)
1
20
0
2
Order By: Relevance
“…The results showed that the microbial structure varied by cheese type, animal milk source, additives used, and whether the milk was pasteurized. Other traditional cheeses have also been studied, such as Latin-style cheese, Kazakhstan cheese, Italian cheese, and Mexican cheese (Lusk et al, 2012;Gonz谩lez-C贸rdova et al, 2016;Li et al, 2017;Silvetti et al, 2017). However, the microbial communities present in Buryatian cheeses have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the microbial structure varied by cheese type, animal milk source, additives used, and whether the milk was pasteurized. Other traditional cheeses have also been studied, such as Latin-style cheese, Kazakhstan cheese, Italian cheese, and Mexican cheese (Lusk et al, 2012;Gonz谩lez-C贸rdova et al, 2016;Li et al, 2017;Silvetti et al, 2017). However, the microbial communities present in Buryatian cheeses have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…This method has successfully been applied to evaluate the safety of infant formula, based on the bacterial population of traditional fermented koumiss and milk products enhanced with probiotics (Gesudu et al, 2016;Zheng et al, 2016;Xu et al, 2017). However, few studies have applied the PacBio SMRT sequencing technology to study the microbiota composition of traditional cheeses, with the exception of a previous study that depicted the bacterial profiles in artisan cheese from Kazakhstan (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota profile of a fermented product does not only reveal its potential functions but also information regarding food safety. The application of the PacBio single-molecule, real-time (SMRT) sequencing technology in full-length 16S rRNA profiling has been applied to depict the microbiota composition in different samples, including silage (Bao et al, 2016), koji (Hui et al, 2017), infant milk powder (Zheng et al, 2016), and cheese (Li et al, 2017). This technique is advantageous over other currently available strategies in microbiota profiling because of its capacity in producing long sequence reads and thus providing high-resolution taxonomic profiles to the species level.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studying the intrinsic microbiota composition is of high practical significance for the industrialization and promotion of camel milk. High-throughput sequencing has become a common technique to investigate microbial communities present in food products including milk (Ercolini, 2013;Li et al, 2017;Jin et al, 2018). It overcomes the limitation of isolating fastidious microbes using culture-dependent methods.…”
Section: Analyses Of Physicochemical Properties Bacterial Microbiotamentioning
confidence: 99%